2015
DOI: 10.1007/s10646-015-1457-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of norfloxacin on hepatic genes expression of P450 isoforms (CYP1A and CYP3A), GST and P-glycoprotein (P-gp) in Swordtail fish (Xiphophorus Helleri)

Abstract: The presence of antibiotics including norfloxacin in the aquatic environment may cause adverse effects in non-target organisms. But the toxic mechanisms of fluoroquinolone to fish species are still not completely elucidated. Thus, it is essential to investigate the response of fish to the exposure of fluoroquinolone at molecular or cellular level for better and earlier prediction of these environmental pollutants toxicity. The sub-chronic toxic effects of norfloxacin (NOR) on swordtail fish (Xiphophoru s helle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…2018), bath at environmental relevant levels (Liang et al . 2015) and injection (Vaccaro et al . 2003; Hu et al .…”
Section: Detoxification and Biotransformation Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…2018), bath at environmental relevant levels (Liang et al . 2015) and injection (Vaccaro et al . 2003; Hu et al .…”
Section: Detoxification and Biotransformation Responsesmentioning
confidence: 99%
“…2012) and gender (Liang et al . 2015) specific differences. Such suppression indicates limited ability to counteract excessive oxidative stress caused by antibiotics, which may sustain their toxicity and thus damage fish tissues (Smith et al .…”
Section: Detoxification and Biotransformation Responsesmentioning
confidence: 99%
“…Liang et al [90] measured the subchronic toxic effects of NOR on a swordtail fish by measuring mRNA expression of cytochrome P450 1A (CYP1A), cytochrome P-450 3A (CYP3A), glutathione S-transferase (GST), P-glycoprotein (P-gp), and their corresponding enzyme activities. Results showed that NOR significantly affected the expression of CYP1A, CYP3A, GST, and P-gp genes in swordtails.…”
Section: Molecular Mechanisms Of Fq Toxicitymentioning
confidence: 99%
“…CYP1A enzyme activities are inhibited by many factors, including the environment, diet, and co-administration of drugs. For example, CYP1A enzyme activities are strongly inhibited by quinolones ( e.g ., lomefloxacin, ciprofloxacin, and gatifloxacin), fluvoxamine, furafylline, oral contraceptives, and some traditional Chinese medicines [1011121314]. Al-Mohizea et al [10] studied the effects of Acacia catechu on the pharmacokinetics of theophylline, a CYP1A-enzyme-specific substrate, in rabbits.…”
mentioning
confidence: 99%
“…They reported that all of the fluoroquinolones studied inhibited CYP1A in a non-competitive manner and that several altered CYP1A activity via mechanism-based inhibition that is irreversible and cumulative. Thus, prolonged treatment with these substances may inhibit CYP1A activity in a manner that can result in serious drug-drug interactions [12]. Wijnands et al [14] reported that total body clearance of theophylline in humans was significantly decreased by enoxacin, ciprofloxacin, and pefloxacin.…”
mentioning
confidence: 99%